Characterization of discontinuous carbon fiber liquid molded PA-6 composites via strategic placement of additional reinforcements. (November 2018) - Brahma, Siddhartha; Patel, Vikas; Pillay, Selvum; Ning, Haibin; Thomas, Vinoy
The flexibility of processing PA6-based discontinuous carbon fiber panels using vacuum-assisted resin transfer molding was studied. The ease of incorporating various reinforcements namely baseline, tow in the center of preform, fabric in the center of preform and fabric on the outside as skin was investigated. Mechanical characterization was conducted on all the variations made. There was an average increase of about 3%, 20% and 47% in the tensile properties of tow in the center, fabric in the center and fabric on the outside as skin, respectively, as compared to the baseline. A similar increase in properties was noticed in its flexural and impact strength. The data showed a correlation between the mechanical properties and the total surface area of additional reinforcements used. As the surface area of the reinforcement increased, the mechanical properties increased as well. It also showed that reinforcements on the surface of the preform as a skin performed the best. DMA analysis showed the effect of reinforcement on the storage modulus and tan delta across temperatures ranging from 30°C to 150°C. SEM analysis showed that the fibers and the additional reinforcements were coated with PA6 which translated into consistent mechanical performance.